Psikologi Pendidikan Dalam Peningkatan Mutu Pendidikan di SMA N 1 Kota Metro - Hanwar Priyo Handoko (Jurnal Dewantara, 2019)
Learning the psychology of education for teachers is very important in order to be able to deal with some of the characteristics of students so that there is no distortion in teaching and reduce the occurrence of violence in students committed by a teacher. This type of research is field research, while the nature of this study is qualitative. describe how the implementation of educational psychology in improving the quality of education in SMA N 1 Metro City. Implementation of educational psychology that is applied by teachers in various ways, namely the use of various methods in learning, the use of tools and media, promoting interaction with students, providing guidance, motivation, attention, and direction, and teachers give values to their students fairly. The teacher's effort in overcoming challenges in the learning process is by entering early lessons and giving advice.